Chemical Exchange Saturation Transfer (CEST) Agents: Quantum Chemistry and MRI. Issue 1 (30th November 2015) - Li, Jikun; Feng, Xinxin; Zhu, Wei; Oskolkov, Nikita; Zhou, Tianhui; Kim, Boo Kyung; Baig, Noman; McMahon, Michael T.; Oldfield, Eric
Abstract: Diamagnetic chemical exchange saturation transfer (CEST) contrast agents offer an alternative to Gd 3+ ‐based contrast agents for MRI. They are characterized by containing protons that can rapidly exchange with water and it is advantageous to have these protons resonate in a spectral window that is far removed from water. Herein, we report the first results of DFT calculations of the 1 H nuclear magnetic shieldings in 41 CEST agents, finding that the experimental shifts can be well predicted ( R 2 =0.882). We tested a subset of compounds with the best MRI properties for toxicity and for activity as uncouplers, then obtained mice kidney CEST MRI images for three of the most promising leads finding16 (2, 4‐dihydroxybenzoic acid) to be one of the most promising CEST MRI contrast agents to date. Overall, the results are of interest since they show that 1 H NMR shifts for CEST agents—charged species—can be well predicted, and that several leads have low toxicity and yield good in vivo MR images. Abstract : Compare and contrast : The use of DFT calculations permits good predictions of chemical shifts in CEST MRI agents. The most promising leads are nontoxic and have excellent activity in mice kidney MR imaging (see figure).